Differential mobile robot controller study: a low cost experiment based on a small arduino based prototype - Gonçalves, José (2017)
In this paper it is presented a low cost experiment based on a small Arduino based prototype. The chosen educational challenge is a classical introductory experiment, that consists in following a line with a mobile robot. The presented experiment has as goal to introduce students to mobile robotics, having as base a challenge and a kinematics that are commonly applied in Junior competitions. A group of students participated in a workshop that consisted, initially, in a lecture where tutors explained the differential robot kinematics and how to develop a controller for the proposed challenge. Then the students, after the theoretical introduction, implemented the proposed robot controller.